Isotropy in Spatial Orientation of Galaxies in the SDSS CGG 23005 having Redshift 0.11 (NUTA Journal, 2024)
We studied the Spatial orientations of 1015 SDSS galaxies in the SDSS CGG 23005 using 7th data release. Our main goal is to examine the non-random effect and to study spatial orientation of galaxies in the SDSS CGG 23005, of three different scenarios ('hierarchy model', 'primordial vorticity theory', and 'pancake model') using Godlowski theory. To check for anisotropy or isotropy we used three statistical tests: Chi-square, Auto-correlation, and the Fourier test. By analyzing the result evolution of galaxies in the SDSSCGG 23005 supports the "hierarchy model"( Peebles 1969).